Clinical outcomes of single full-coverage lithium disilicate restorations: A systematic review - Yousif A. Al-Dulaijan; Hussain M. Aljubran; Nabras M. Alrayes; Hajer A. Aldulaijan; Mishali AlSharief; Faisal E. Aljofi; Maria S. Ibrahim (Saudi Dental Journal, 2023)
Introduction: Lithium disilicate glass–ceramic (LDC) restorations exhibit microorganism infiltration, recurrent caries, pulpal lesions, periodontal inflammation, and cement exposure to the oral environment over time. All these factors lead to restoration failure. This systematic review aimed to investigate the clinical outcomes of LDC full-coverage crowns (FCC) in permanent teeth compared with those of other full-coverage restoration materials. Materials & Methods: Search strategies were developed for four databases: Web of Science, OVID, PubMed, and Scopus. Data extraction and quality appraisals were performed by two independent reviewers. Data on the presence of caries, post-operative sensitivity, and periodontal changes were extracted from the included clinical studies. In addition to the outcome measures, data on the sample size, study groups, method of restoration fabrication, type of impression, and type of abutment were recorded. Results: We retrieved 3989 records for the title and abstract screening. Of these, 19 clinical studies met the inclusion criteria. The overall quality of the included studies indicates a low risk of bias. Most studies reported no pulpal involvement, recurrent caries, or post-operative sensitivity and presented a favorable periodontal response after the cementation of LDC-FCC during different follow-up periods. Conclusion: Based on the endodontic and periodontic clinical responses of natural tooth abutments and their supporting periodontium, LDC-FCC can be considered a clinically successful restorative option.